KAJIAN PEMBERIAN PUPUK P, PUPUK MIKRO DAN PUPUK ORGANIK TERHADAP SERAPAN P DAN HASIL KEDELAI (Glycine max L.) VARIETAS KABA DI INSEPTISOL GUNUNG GAJAH KLATEN - Supriyadi Supriyadi; Sri Hartati; Almar Aminudin (Caraka Tani: Journal of Sustainable Agriculture, 2014)
Research purposes to determine the response of soybean varieties Kaba under protected forest tree stands besides soybean crop response to P fertilizer and manure fertilizer micro coupled with organic fertilizer uptake and utilization of P element to the low light under protected forest tree stands. The research was conducted in JulyDecember 2011. Experiments using Randomized Complete (RAKL) factorial consists of 3 factors, namely fertilization with manure P 1, factor 2 micro fertilization with manure, and a factor of 3 fertilizing with organic fertilizers. Each treatment combination was repeated 3 kali.Faktor first fertilizer P fertilizer P The first factor consists of three levels, namely P1 (50 kg / ha), P2 (75 kg / ha), and P3 (100 kg / ha). The second factor consists of 2 fertilizer micro level, ie M1 (0.5 l / ha) and M2 (1.5 l / ha). The third factor of organic fertilizer consisting of 2 levels, ie O0 (0 tonnes / ha) and O1 (5 tonnes / ha). Data analysis using the F test level of 5% followed by comparison test (DMRT) level of 5%. The results show the interaction between P fertilizer, micro fertilizer and organic fertilizer effect on soil pH, P uptake, and the number of pods. P fertilizer on fertilizer and organic fertilizer micro effects and no significant effect on available P and heavy pod soybeans (Glycine max L.).